2016
DOI: 10.14740/wjon954w
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Carcinoma: the Disease that Kills

Abstract: The purpose of this case report is to demonstrate the clinical symptoms and laboratory changes that have occurred very late and were very few in number even the imaging studies performed at that time showed an intensive local tumor growth associated with the wide infiltration of the both adjacent and distant upper abdominal structures. A 71-year-old male patient who was a chronic alcohol abuser and ex smoker (quit smoking 8 years earlier) presented with symptoms of mild pain on epigastric region that irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…However, the median survival time of PDAC is less than 17 months, and so the model is not suitable for majority patients with pancreatic cancer [ 9 ]. The nomogram developed by Brennan et al [ 5 ] included a large number of variables, such as tumor margins on resection, patient weight loss, and portal vein resection in the study, but the C-index of the model was 0.64, which may be explained by the fact that the study included distal PDAC which has a worse prognosis that PDAC of the head of the pancreas [ 18 ]. The nomogram established by Xu et al [ 11 ] showed high predictive accuracy for the prognosis of PDAC, but the development of the model was based on data from a single center with a small study population, and the standard values of the variables were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, the median survival time of PDAC is less than 17 months, and so the model is not suitable for majority patients with pancreatic cancer [ 9 ]. The nomogram developed by Brennan et al [ 5 ] included a large number of variables, such as tumor margins on resection, patient weight loss, and portal vein resection in the study, but the C-index of the model was 0.64, which may be explained by the fact that the study included distal PDAC which has a worse prognosis that PDAC of the head of the pancreas [ 18 ]. The nomogram established by Xu et al [ 11 ] showed high predictive accuracy for the prognosis of PDAC, but the development of the model was based on data from a single center with a small study population, and the standard values of the variables were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pancreatic carcinomas arising from the tail are less common and present later, usually with abdominal pain, back pain, and weight loss. Pancreatic cancer of the tail is often undiagnosed or misdiagnosed and thus is associated with a higher mortality rate due to its frequent late presentation [3, 4, 7, 8]. An earlier diagnosis depends on a better understanding of the clinical course of the disease; however, much of the current literature focuses on pancreatic head adenocarcinomas due to their higher incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75% of all pancreatic carcinomas arise in the head of the pancreas; 15–20% arise in the body; and 5–10% arise in the tail [4]. Previous research has demonstrated meaningful differences in presentation and mortality between carcinomas arising in the pancreatic head versus in the pancreatic body and tail [5].…”
Section: Introductionmentioning
confidence: 99%
“…When symptoms do arise, they are often vague and vary depending on the tumor location [2]. Around 75% of all pancreatic carcinomas are found in the head, 15%-20% in the body, and 5%-10% in the tail [3]. Old study has found significant variations in the appearance and mortality of pancreatic head carcinomas vs carcinomas of the pancreatic body and tail [4].…”
Section: Introductionmentioning
confidence: 99%